Prevalence and Potential Determinants of Primary Infertility Among Reproductive-Age Couples: A Cross-Sectional Study - Wiqodatul Ummah; Ahisa Novianti; Lailatul Rahmawati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Infertility is defined as the failure to establish a clinical pregnancy following at least 12 months of regular, unprotected sexual intercourse. This condition impacts an estimated 15% of couples of reproductive-age worldwide. The objective of this study was to investigate the prevalence and associated factors of primary infertility among couples aged 18 to 49 years. An analytical cross-sectional study was conducted from November 2025 to January 2026, involving 398 couples of reproductive-age selected through purposive sampling. Data were analyzed using multivariable logistic regression. The prevalence of primary infertility was 15.6% (95% CI: 12.2%-19.5%). Female age ?35 years was the strongest determinant (AOR=5.24; 95% CI: 2.18-12.60). Significant socio-economic factors included university education (AOR=2.94; 95% CI: 1.26-6.86) and higher income (AOR=2.36; 95% CI: 1.18-4.72). Modifiable lifestyle factors such as male smoking (AOR=2.86), female obesity (AOR=2.64), male obesity (AOR=2.18), and female stress (AOR=1.42) increased infertility risk, whereas high physical activity was protective (AOR=0.38). Health-related determinants included irregular menstruation (AOR=2.94), polycystic ovary syndrome (AOR=3.42), female sexually transmitted infection history (AOR=2.48), and varicocele (AOR=2.86). The prevalence of primary infertility among reproductive-age couples in Malang Regency was 15.6% and was independently associated with demographic, socio-economic, lifestyle, and health-related factors. Female age ?35 years was the strongest determinant, while modifiable factors including smoking, obesity, physical inactivity, stress, and sexually transmitted infections highlight the need for early screening, reproductive counseling, lifestyle modification, and STI prevention.